Metabolic responses to dietary leucine restriction involve remodeling of adipose tissue and enhanced hepatic insulin signaling. (8th December 2015) - Wanders, Desiree; Stone, Kirsten P.; Dille, Kelly; Simon, Jacob; Pierse, Alicia; Gettys, Thomas W.
Abstract: Dietary leucine was incrementally restricted to test whether limiting this essential amino acid (EAA) would fully reproduce the beneficial responses produced by dietary methionine restriction. Restricting leucine by 85% increased energy intake and expenditure within 5 to 7 days of its introduction and reduced overall accumulation of adipose tissue. Leucine restriction (LR) also improved glucose tolerance, increased hepatic release of fibroblast growth factor 21 into the blood stream, and enhanced insulin‐dependent activation of Akt in liver. However, LR had no effect on hepatic lipid levels and failed to lower lipogenic gene expression in the liver. LR did affect remodeling of white and brown adipose tissues, increasing expression of both thermogenic and lipogenic genes. These findings illustrate that dietary LR reproduces many but not all of the physiological responses of methionine restriction. The primary differences occur in the liver, where methionine and LR cause opposite effects on tissue lipid levels and expression of lipogenic genes. Altogether, these findings suggest that the sensing systems which detect and respond to dietary restriction of EAAs act through mechanisms that both leucine and methionine are able to engage, and in the case of hepatic lipid metabolism, may be unique to specific EAAs such as methionine. © 2015 BioFactors, 41(6):391–402, 2015